Enema reduction of intussusception: the success rate of hydrostatic and pneumatic reduction - Khorana J; Singhavejsakul J; Ukarapol N; Laohapensang M; Wakhanrittee J; Patumanond J (Dove Medical Press, 2015)
Jiraporn Khorana,1 Jesda Singhavejsakul,1 Nuthapong Ukarapol,2 Mongkol Laohapensang,3 Junsujee Wakhanrittee,4 Jayanton Patumanond5 1Division of Pediatric Surgery, Department of Surgery, 2Division of Gastroenterology, Department of Pediatrics, Chiang Mai University Hospital, Chiang Mai, 3Division of Pediatric Surgery, Department of Surgery, Siriraj Hospital, Mahidol University, Bangkok, 4Division of Pediatric Surgery, Department of Surgery, Thammasat University Hospital, 5Center of Excellence in Applied Epidemiology, Thammasat University Hospital, Pathumthani, Thailand Purpose: Intussusception is a common surgical emergency in infants and children. The incidence of intussusception is from one to four per 2,000 infants and children. If there is no peritonitis, perforation sign on abdominal radiographic studies, and nonresponsive shock, nonoperative reduction by pneumatic or hydrostatic enema can be performed. The purpose of this study was to compare the success rates of both the methods.Methods: Two institutional retrospective cohort studies were performed. All intussusception patients (ICD-10 code K56.1) who had visited Chiang Mai University Hospital and Siriraj Hospital from January 2006 to December 2012 were included in the study. The data were obtained by chart reviews and electronic databases, which included demographic data, symptoms, signs, and investigations. The patients were grouped according to the method of reduction followed into pneumatic reduction and hydrostatic reduction groups with the outcome being the success of the reduction technique.Results: One hundred and seventy episodes of intussusception occurring in the patients of Chiang Mai University Hospital and Siriraj Hospital were included in this study. The success rate of pneumatic reduction was 61% and that of hydrostatic reduction was 44% (P=0.036). Multivariable analysis and adjusting of the factors by propensity scores were performed; the success rate of pneumatic reduction was 1.48 times more than that of hydrostatic reduction (P=0.036, 95% confidence interval [CI] =1.03–2.13).Conclusion: Both pneumatic and hydrostatic reduction can be performed safely according to the experience of the radiologist or pediatric surgeon and hospital setting. This study showed that pneumatic reduction had a higher success rate than hydrostatic reduction. Keywords: intussusception, pneumatic reduction, hydrostatic reduction, success rate